ANALISIS PENGARUH FAKTOR FUNDAMENTAL DAN RISIKO SISTEMATIK TERHADAP RETURN SAHAM PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA (BEI) (Students' Journal of Accounting and Banking, 2013)
This study aims to obtain a proven fact that explains the influence of fundamental factors (Return On Assets, Dividend Payout Ratio, Current Ratio, Return On Equity, Debt to Equity Ratio, Book Value) and the systematic risk on the stock return of go public manufacturing companies on the Stock Exchange either partially or simultaneously, as well as to obtain a proven fact that explains the factors that are most influential and dominant on stock return in such manufacturing company. The population in this study is all manufacturing companies listed on the Indonesia Stock Exchange during the ears 2009 to 2011. By purposive sampling technique, obtained a sample of 87 companies. Data were analyzed by multiple linear regression analysis techniques. The results of this study indicate that the Return On Assets (ROA) has negative and significant influence on Stock Return, Dividend Payout Ratio (DPR) has negative and significant impact on Stock Return, Current Ratio (CR) has positive and significant Stock Return, Return On Equity (ROE) has negative and significant impact on Return Stock, Debt to Equity Ratio (DER) had no significant effect on Stock Return, Book Value (BV) has positive and significant impact on Stock Return and Systematic Risk has positive and significant influence on Stock Return. Keywords: Fundamental factors, Return On Assets, Dividend Payout Ratio, Current Ratio, Return On Equity, Debt to Equity Ratio, Book Value, systematic risk, stock returns